Peran Media Sosial Dalam Membangun Dakwah Islam yang Efektif - Ahmad Faza Fauzan Saragih; Rony Fernando Sagala; Erwan Effendi (Dakwatussifa: Journal of Da'wah and Communication, 2022)
Along with the times and technology, the way of preaching has also changed. Compared to preaching through speech, currently preaching through writing is more urgent and effective to do, namely preaching using social media such as the internet and writings on social media that contain da'wah messages. The advantages of preaching with this model do not make the preaching material disappear even though the preacher, or the writer has died, as the expression of His Majesty Rasulullah SAW, "Indeed the ink of the scholars is better than the blood of the martyrs." However, the purpose of da'wah with this model will be realized if it is supported by effective media. This means that in the da'wah process the preachers do not only present material verbally, but also must deliver their da'wah material via social media so that the material can be read anywhere and anytime, as is the case with the role of social media today. If we look at da'wah at this time, it is necessary to have a critical and in-depth evaluation, because the styles, models, methods and media used also influence the implementation, direction, dynamics and implementation of da'wah. Given the importance of social media as a means of preaching, it is necessary to have specific strategies, methods and approaches for preachers in preaching regarding the use of social media as a means of conveying messages of Islamic da'wah. This journal will contribute thoughts to become an inspiration for preachers to use social media as a means of conveying da'wah messages. Keywords: Social Media, Da'wah, Effective